2022
DOI: 10.3389/fmicb.2022.1031474
|View full text |Cite
|
Sign up to set email alerts
|

Integrated physiological, metabolomic, and proteome analysis of Alpinia officinarum Hance essential oil inhibits the growth of Fusarium oxysporum of Panax notoginseng

Abstract: Fusarium oxysporum is the main pathogen of Panax notoginseng root rot, and chemical fungicides remain the primary measures to control the disease. Plant essential oil (EO) is a volatile plant secondary metabolic product that does not produce any residue to replace chemical pesticide. To comprehensively understand the antifungal mechanism of Alpinia officinarum Hance EO, the physiological indicators, proteome and metabolome were analyzed using F. oxysporum spores and hyphae treated with different EO concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The supernatant of C. gloeosporioides culture broth treated with REO of MIC was taken at 0, 6, 12, 24, 36, 48 and 72 h. The absorbance at 260 nm was measured by a microplate reader in order to characterize the leakage of nucleic acids [26]. The content of soluble protein leakage was determined by Coomassie brilliant blue G-250 staining, and the leakage of soluble reducing sugar in the fungal solution was detected using the colorimetric method of 3,5-dinitrosalicylic acid according to Liu et al [27] with some modifications.…”
Section: Effects On Extracellular Conductivity and Leakage Of Nucleic...mentioning
confidence: 99%
“…The supernatant of C. gloeosporioides culture broth treated with REO of MIC was taken at 0, 6, 12, 24, 36, 48 and 72 h. The absorbance at 260 nm was measured by a microplate reader in order to characterize the leakage of nucleic acids [26]. The content of soluble protein leakage was determined by Coomassie brilliant blue G-250 staining, and the leakage of soluble reducing sugar in the fungal solution was detected using the colorimetric method of 3,5-dinitrosalicylic acid according to Liu et al [27] with some modifications.…”
Section: Effects On Extracellular Conductivity and Leakage Of Nucleic...mentioning
confidence: 99%
“…Liu et al. ( 2022 ) revealed that A. officinarum EOs inhibit the growth of F. oxysporum by disrupting cell membranes and affecting cell division. In addition to EOs of Zingiberaceae plants, Zeng et al.…”
Section: Biological Control Of Root Rot In P Notoginsengmentioning
confidence: 99%